Analysis of the determining factors of muslim tourists' interest in visiting the cultural tourism of Borobudur Temple - Rahmayanti, Dini (Nur Science Institute, 2026)
This study examines the effects of Borobudur heritage brand awareness, Muslim tourists’ perceived value, and halal-friendly attributes on consumer satisfaction and revisit intention at Borobudur Temple. This research used a quantitative approach, with data collected through questionnaires and analyzed using SmartPLS. The findings show that heritage brand awareness, Muslim tourists’ perceived value, halal-friendly facilities, and halal food and beverages influence consumer satisfaction and revisit intention. Halal-friendly social environment and local residents influence consumer satisfaction but do not directly affect revisit intention. Meanwhile, halal services do not affect either consumer satisfaction or revisit intention. The results also indicate that consumer satisfaction has a direct effect on revisit intention and mediates several relationships among the examined variables. However, consumer satisfaction does not mediate the relationship between halal friendliness and revisit intention. These findings provide practical implications for developing Borobudur tourism in a more sustainable, competitive, and inclusive direction, particularly by strengthening services, facilities, and tourism experiences that meet the needs of Muslim tourists.